Truth-myths of New Zealand - Stewart, Georgina Tuari (Springer Science and Business Media LLC, 2023)
This article probes the gap between different cultural perspectives in contemporary Aotearoa New Zealand, a nation-state founded on a bicultural encounter between indigenous Māori and settler British. One source of misunderstandings is a set of distorted versions of historical and social reality that have been promulgated through schooling and national media. These distortions of truth take the form of certain dubious, denigratory ideas about Māori, accepted as commonsense truth by Pākehā (European New Zealanders) to bolster their feelings of security and superiority in relation to Māori. I refer to these ideologies as the ‘truth-myths of New Zealand’ that operate like thought weapons of Whitepower within the apparently harmonious social context of Aotearoa New Zealand, dubbed with a longstanding reputation for the ‘best race relations in the world’. The purpose of this article is to focus in on the truth-myths themselves, represented by three typical statements of key ideas, presenting and explaining each one, and commenting on their significance and ongoing influence in national education, and society more generally.